Fostering Local Economic Development through Agripreneurship in Nepal - Mishra, A. K. (SAIM Journal of Social Science and Technology, 2024)
Agricultural entrepreneurship is crucial for local economic development in Nepal, where a significant portion of the population relies on agriculture. This study explores the multifaceted factors influencing agripreneurship and outlines strategies to enhance this sector. It highlights that while Nepal has abundant agricultural resources, the current infrastructure, market access, and financial services are inadequate, hindering agripreneurial potential. The study identifies that enhancing infrastructure, such as roads, storage facilities, and financial services, is essential for fostering a robust agripreneurial ecosystem. It also emphasizes the importance of improving perceptual factors by increasing the attractiveness of agriculture and reducing the fear of failure through risk mitigation measures. Furthermore, the study underscores the need for investments in educational and vocational training to build intellectual capital and develop relevant business skills. Strengthening market access and fostering a supportive environment through mentorship and networking are also recommended. By implementing these strategies, Nepal can leverage its agricultural resources more effectively, driving local economic development and improving rural prosperity.